2006
DOI: 10.1097/01.inf.0000226941.85500.9b
|View full text |Cite
|
Sign up to set email alerts
|

Nicolau Syndrome After Intramuscular Benzathine Penicillin Treatment

Abstract: Nicolau syndrome (livedoid dermatitis) is a very rare complication of intramuscular injections and manifests as excruciating pain immediately after injection. We describe a 3-year-old boy with diagnosis of Nicolau syndrome after intramuscular benzathine penicillin injection to the midanterior part of the left thigh. He was treated with hyberbaric oxygen and pentoxyphilline in addition to supportive treatment and recovered with no sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 4 publications
0
40
0
Order By: Relevance
“…Use of vasoactive agents such as subcutaneous heparin and oral pentoxifylline has been recognized as beneficial. [8] Topical steroids may be worth trying. Surgical intervention is rarely required.…”
mentioning
confidence: 99%
“…Use of vasoactive agents such as subcutaneous heparin and oral pentoxifylline has been recognized as beneficial. [8] Topical steroids may be worth trying. Surgical intervention is rarely required.…”
mentioning
confidence: 99%
“…Enoxaparin, pentoxyphylline and HBO treatment were given to our patient. To the best of our knowledge, there is only one case report in literature where HBO was used early in the treatment of NS with complete healing [9]. Our patient appears to be the second case of NS that was treated with HBO, but in the late period (after 1 week of diagnosis and after necrosis had ensued).…”
Section: Discussionmentioning
confidence: 89%
“…Rapid administration of steroids, anticoagulants, and vasoactive agents has been emphasized for clinical improvement and regression of the livedoid lesions whereas it has been demonstrated that heparin and pentoxifylline are useless in preventing the development of necrosis [1,3,10,22]. Hyperbaric oxygen treatment may be beneficial at the early onset of disease [10]. If NS is regarded as an unintended intra-arterial injection injury and recognized at early stages, treatment guidelines preceded by Sen et al from the Mayo Clinic may be beneficial [23].…”
Section: Discussionmentioning
confidence: 99%
“…The actual physiopathology of the NS is yet unknown; it has been proposed that the direct arterial damage and vasoconstrictive effects of various drugs may induce inflammation and subsequently cause skin necrosis [2,3]. Agents, such as nonsteroidal anti-inflammatory drugs, steroids, vitamines, benzathine penicillin, hydroxyzine, vaccines i.e., are reported to be potential triggering factors of this clinical entity [2,[4][5][6][7][8][9][10][11][12][13]. There is no consensus on the treatment protocol of the disease.…”
Section: Introductionmentioning
confidence: 99%